PENGARUH ETIKA KARYAWAN DAN PELATIHAN TERHADAP KINERJA KARYAWAN (Studi Kasus Pada Karyawan Coffee Crowd di Kota Medan) - Utami, Siti Sarah; Saskia; Nasution, Aulia Arief (Jurnal Ekonomi Bisnis Digital, 2023)
This type of research is a type of casual associative research, the type of causal associative research (cause and effect) is research that aims to find whether there is a relationship between two or more variables. This research was conducted in one government office, namely the Human Resources Development Agency (BPSDM) of Sumatra Province North which is located on Jln. Ngalengko No.1, Perintis, East Medan District, Medan City, North Sumatra. The population is the whole of the research subjects, while the sample is part of the population. Values ​​that are calculated and obtained from this population are called parameters. population taken is 150 employees. Samples were taken by 100 employees using the Slovin formula sampling technique. The data source used was primary data. Researchers also collect data by observing or observing the BPSDM office. Sub structure I Variable Competence (X1) of 0.552 states that for every addition of 1% Competence, it will increase Commitment by 0.552 or 55.2%, and vice versa if Competence decreases by 1% then Commitment will be predicted to decrease by 0.552 or 55.2%, Variable Work Ethic (X2) of -0.053 states that for every 1% addition of Work Ethic, it will not increase Commitment by -0.053 or 05.3%, and vice versa if Work Ethic decreases by 1%, Commitment will not be predicted to decrease by -0.053 or 05 .3%, Substructure II Competency Variable (X1) of 0.128 states that for every addition of 1% Competence, it will increase Performance by 0.128 or 12.8%, and vice versa if Competence decreases by 1% then Performance will be predicted to decrease by 0.128 or 12, 8%, the Work Ethic Variable (X2) of -0.059 states that for every addition of 1% Work Ethic, it will not increase Performance by -0.059 or -05.9%, and vice versa if Work Ethic decreases by 1% then the performance will be predicted not to decrease by -0.059 or -05.9%. The Commitment Variable (Z) of 0.532 states that for every 1% addition of Commitment, it will increase Performance by 0.532 or 53.2%, and vice versa if the Product Price decreases by 1% then Performance will be predicted to decrease by 0.532 or 53.2%.